A nationwide real-world study on dynamic ustekinumab dosing and concomitant medication use among Crohn's disease patients in Finland - Sipponen Taina; af Björkesten Clas-Göran; Hallinen Taru; Ilus Tuire; Soini Erkki; Eberl Anja; Heikura Mikko; Kellokumpu Mikko; Koskela Ritva; Nielsen Christian; Nuutinen Heikki; Heikkinen Markku; et al. (TAYLOR & FRANCIS LTD, 2022)
Background Real-world evidence to support optimal ustekinumab dosing for refractory Crohn's disease (CD) patients remains limited. Data from a retrospective nationwide chart review study was utilized to explore ustekinumab dosing dynamics and optimization, identify possible clinical predictors of dose intensification, and to evaluate ustekinumab trough concentrations (TCs) and concomitant medication use in Finland.
Methods Information gathered from17 Finnish hospitals included clinical chart data from 155 adult CD patients who received intravenous ustekinumab induction during 2017-2018. Data on ustekinumab dosing and TCs, concomitant corticosteroid and immunosuppressant use, and antiustekinumab antibodies were analyzed in a two-year follow-up, subject to availability.
Results  Among 140 patients onustekinumab maintenance therapy, dose optimization was required in 55(39%) of the patients, and 41/47 dose-intensified patients (87%) persisted on ustekinumab. At baseline, dose-intensified patient group had significantly higher C-reactive protein (CRP) levels, and at week 16, significantly lower ustekinumab TCs than in patients without dose intensification. Irrespective of dose optimization, a statistically significant reduction in the use of corticosteroids was observed at both 16 weeks and one year, coupled with an increased proportion of patients on ustekinumab monotherapy. Antiustekinumab antibodies were undetectable in all 28 samples from 25 patients collected throughout the study period.
Conclusions Nearly a third of all CD patients on ustekinumab maintenance therapy, with a history of treatment-refractory and long-standing disease, required dose intensification. These patients persisted on ustekinumab and had significant reduction of corticosteroid use. Increased baseline CRP was identified as the sole indicator of dose intensification.